Coal gangue-based solid waste pavement base mixture and preparation method thereof

CN122916554APending Publication Date: 2026-10-16CHINESE ACAD OF ENVIRONMENTAL PLANNING
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320865.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本申请提供了一种煤矸石基固废路面基层混合料及其制备方法,以解决如下技术问题:如何同时提高煤矸石集料在路面基层中的力学性能与耐久性能

Benefits of technology

(1)通过纳米SiO2以Si-O-Si共价键化学接枝于煤矸石集料表面,使纳米颗粒牢固锚定于集料而无法在拌合过程中脱附,纳米SiO2持续发挥火山灰活性与微集料填充效应,显著降低界面过渡区孔隙率并强化集料-胶浆界面结合力,使力学强度提升;同时共价键接枝层在集料表面形成致密的疏水屏障,有效阻隔水分通过集料表面微孔隙侵入集料内部,从源头抑制煤矸石的吸水膨胀与崩解粉化,使水稳定性提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916554A_ABST
    Figure CN122916554A_ABST
Patent Text Reader

Abstract

The application provides a coal gangue-based solid waste pavement base mixture and a preparation method thereof, and belongs to the field of low-carbon building materials. After the coal gangue aggregate is activated by alkali, nano-SiO2 is chemically grafted on the surface of the aggregate by silane coupling agent KH-550, and then nano-CaCO3 is deposited on the surface of the SiO2 layer in situ by a carbonization method to form double nano gradient modified aggregate. After the modified aggregate is pre-compacted with an alkali activator, the modified aggregate is secondarily mixed with Portland cement, phosphogypsum, polycarboxylic acid water reducing agent and ethylene-vinyl acetate copolymer latex powder, and then is formed into a pavement base mixture through vibration compaction and curing. The 7d unconfined compressive strength of the mixture reaches 4.5-6.5MPa, and the 28d unconfined compressive strength reaches 6.0-8.5MPa. The utilization rate of the coal gangue solid waste reaches more than 70%, the carbon emission is significantly reduced, and the mixture has excellent road performance and low-carbon environmental protection benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of low-carbon building materials technology, and in particular to a coal gangue-based solid waste road base mixture and its preparation method. Background Technology

[0002] Material consumption during highway construction and maintenance is a major source of carbon emissions, with cement and steel being the primary contributors. Therefore, the large-scale utilization of industrial solid waste and the reduction of traditional high-carbon-emission building materials such as cement in highway construction have become important technological pathways for the transportation industry to achieve carbon reduction targets. Coal gangue is a solid waste generated during coal mining and washing. Large-scale ground stockpiling of coal gangue not only occupies land resources but also poses ecological and environmental risks such as spontaneous combustion, dust, and soil and water pollution. Using coal gangue as a road construction material in the base layer of highway pavements is an effective way to achieve large-scale utilization of coal gangue and carbon emission reduction.

[0003] Currently, there is a certain research foundation for the technical route of preparing road base course mixtures using cement-stabilized coal gangue or alkali-activated coal gangue. However, coal gangue aggregates generally have inherent defects such as high water absorption, large crushing value, and easy disintegration and pulverization upon contact with water; at the same time, the surface of coal gangue lacks active sites to form a strong chemical bond with cement hydration products, resulting in high porosity and weak bonding force in the transition zone between aggregate and mortar. These problems make it difficult for existing coal gangue-based road base course mixtures to meet the technical requirements of high-grade highway pavement base courses in terms of key road performance aspects such as mechanical strength, water stability, and resistance to shrinkage cracking. Therefore, how to simultaneously improve the mechanical properties and durability of coal gangue aggregates in road base courses is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0004] This application provides a coal gangue-based solid waste road base mixture and its preparation method to solve the following technical problem: how to simultaneously improve the mechanical properties and durability of coal gangue aggregate in road base.

[0005] In a first aspect, this application provides a method for preparing a coal gangue-based solid waste roadbed mixture, the method comprising the following steps: S1. The coal gangue aggregate is soaked in NaOH solution for activation pretreatment to obtain activated coal gangue; S2. Add nano-SiO2 and silane coupling agent KH-550 to an ethanol-water mixed solvent to obtain a functionalized nano-SiO2 dispersion. S3. The activated coal gangue and the functionalized nano-SiO2 dispersion are stirred and reacted to obtain nano-SiO2 grafted coal gangue. S4. The nano-SiO2-grafted coal gangue is immersed in Ca(OH)2 solution, and then CO2 gas is introduced into the system to carry out carbonization reaction to obtain dual nanogradient modified coal gangue. S5. The dual nanogradient modified coal gangue is mixed with alkali activator and water and then subjected to static curing treatment to obtain pre-cured mixture. S6. The pre-cured mixture is subjected to forced mixing with silicate cement, phosphogypsum, water, polycarboxylate superplasticizer, and ethylene-vinyl acetate copolymer latex powder to obtain a mixture. S7. The mixture is subjected to vibration compaction and curing treatment to obtain coal gangue-based solid waste road base mixture.

[0006] Optionally, by weight, in the coal gangue-based solid waste road base mixture, the amount of coal gangue aggregate is 65-80 parts, silicate cement is 8-12 parts, phosphogypsum is 3-6 parts, alkali activator is 0.9-1.8 parts, polycarboxylate superplasticizer is 0.5-1.0 parts, and ethylene-vinyl acetate copolymer latex powder is 0.15-0.45 parts.

[0007] Optionally, the concentration of the NaOH solution is 10–20 wt%. The activation pretreatment is performed at a temperature of 60–80°C for 2–4 hours.

[0008] Optionally, the mass of the nano-SiO2 is 0.4% to 0.9% of the mass of the coal gangue aggregate; The mass of the silane coupling agent KH-550 is 5% to 10% of the mass of the nano-SiO2.

[0009] Optionally, the temperature of the stirring reaction is 80–100°C, and the time is 1–2 hours.

[0010] Optionally, the concentration of the Ca(OH)2 solution is 0.02–0.05 mol / L, and the soaking time is 10–30 min.

[0011] Optionally, the CO2 gas has a purity of ≥99%, a flow rate of 0.5–2.0 L / min, an introduction time of 10–40 min, a reaction temperature of 25–60 °C, and the reaction endpoint is when the pH of the system drops to 10.0–10.5.

[0012] Optionally, the alkaline activator is a composite activator of NaOH and water glass, wherein the mass ratio of NaOH to water glass is 1:(1-3), and the modulus of water glass is 1.0-1.5.

[0013] Optionally, the particle size range of the coal gangue aggregate is 0.075–31.5 mm, and a four-stage gradation is adopted. By mass fraction, 31.5–19 mm accounts for 25%–35%, 19–9.5 mm accounts for 35%–45%, 9.5–4.75 mm accounts for 10%–15%, and less than 4.75 mm accounts for 10%–15%.

[0014] Secondly, this application provides a coal gangue-based solid waste road base course mixture prepared by any one of the methods described in the first aspect, wherein the 7-day unconfined compressive strength of the coal gangue-based solid waste road base course mixture is 4.5–6.5 MPa, and the 28-day unconfined compressive strength is 6.0–8.5 MPa.

[0015] The technical solutions provided in this application have the following advantages compared with the prior art: (1) By chemically grafting nano-SiO2 onto the surface of coal gangue aggregate with Si-O-Si covalent bonds, the nanoparticles are firmly anchored to the aggregate and cannot be desorbed during the mixing process. The nano-SiO2 continues to exert the pozzolanic activity and micro-aggregate filling effect, significantly reducing the porosity of the interface transition zone and strengthening the bonding force between the aggregate and the mortar interface, thereby improving the mechanical strength. At the same time, the covalent bond graft layer forms a dense hydrophobic barrier on the surface of the aggregate, effectively preventing water from penetrating into the interior of the aggregate through the micropores on the surface of the aggregate, inhibiting the water absorption, expansion and disintegration of coal gangue from the source, thereby improving water stability.

[0016] (2) By depositing a nano-CaCO3 shell in situ on the surface of the nano-SiO2 layer, a dual nano-gradient structure of aggregate-covalent bond-nano-SiO2 inner layer-Nano-CaCO3 shell is constructed. The inner layer SiO2 continuously reacts with calcium hydroxide in the middle and late stages of hydration to generate additional hydrated calcium silicate, while the outer layer CaCO3 provides a nucleation effect in the early stage of hydration to accelerate cement hydration. The two complement each other in terms of strength throughout the entire age, ensuring both early and late strength. At the same time, the micro-aggregate filling effect of the outer layer CaCO3 further densifies the pore structure of the interface transition zone, blocking the intrusion channels of water and harmful ions, and improving impermeability and freeze-thaw resistance.

[0017] (3) By using an alkali activator and phosphogypsum to form an alkali-sulfate composite activation system, the potential cementing activity of aluminosilicate minerals in coal gangue is fully activated, generating hydrated calcium silicate, hydrated sodium aluminosilicate, hydrated calcium aluminosilicate gel and ettringite crystals. Multiple hydration products interpenetrate and grow synergistically at the microscale, making the cementing network denser and its strength continuously increasing. At the same time, the dense hydration product network effectively wraps the surface of coal gangue aggregate, isolates the contact between water and the minerals inside the aggregate, inhibits the further hydration expansion of active components in coal gangue in a humid environment, and improves volume stability and long-term durability.

[0018] (4) By using ethylene-vinyl acetate copolymer latex powder to form a polymer film when it comes into contact with water, the ester groups on its molecular chain form dense hydrogen bonds with the amino groups exposed on the surface of grafted nano-SiO2, realizing the tight combination of the flexible polymer film and the rigid inorganic nano-gradient interface. This composite interface effectively transmits and disperses stress when subjected to load, avoiding stress concentration in the interface area, thus improving crack resistance and mechanical strength simultaneously. At the same time, the flexible properties of the polymer film buffer the reciprocating stress of coal gangue aggregate during water absorption expansion and drying shrinkage, reducing the formation and expansion of drying shrinkage cracks, effectively suppressing drying shrinkage, and improving long-term durability. Attached Figure Description

[0019] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0020] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 A schematic flowchart illustrating a method for preparing a coal gangue-based solid waste roadbed mixture, provided in an embodiment of this application; Figure 2 Infrared spectra of raw coal gangue, nano-SiO2 grafted coal gangue, and dual nanogradient modified coal gangue provided in Example 1 of this application. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0023] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0024] Figure 1 This is a schematic flowchart illustrating a method for preparing a coal gangue-based solid waste roadbed mixture, as provided in an embodiment of this application.

[0025] like Figure 1As shown, this application provides a method for preparing a coal gangue-based solid waste road base course mixture, the method comprising the following steps: S1. The coal gangue aggregate is soaked in NaOH solution for activation pretreatment to obtain activated coal gangue; S2. Add nano-SiO2 and silane coupling agent KH-550 to an ethanol-water mixed solvent to obtain a functionalized nano-SiO2 dispersion. S3. The activated coal gangue and the functionalized nano-SiO2 dispersion are stirred and reacted to obtain nano-SiO2 grafted coal gangue. S4. The nano-SiO2-grafted coal gangue is immersed in Ca(OH)2 solution, and then CO2 gas is introduced into the system to carry out carbonization reaction to obtain dual nanogradient modified coal gangue. S5. The dual nanogradient modified coal gangue is mixed with alkali activator and water and then subjected to static curing treatment to obtain pre-cured mixture. S6. The pre-cured mixture is subjected to forced mixing with silicate cement, phosphogypsum, water, polycarboxylate superplasticizer, and ethylene-vinyl acetate copolymer latex powder to obtain a mixture. S7. The mixture is subjected to vibration compaction and curing treatment to obtain coal gangue-based solid waste road base mixture.

[0026] It should be noted that S1 (alkali activation) involves etching the surface of coal gangue aggregate with NaOH solution at 60-80℃, dissolving the surface amorphous silicon-aluminum components, exposing and generating a large number of silanol (-SiOH) and aluminumol (-AlOH) active sites, providing a chemical reaction basis for the subsequent covalent grafting of nano-SiO2.

[0027] In an ethanol / water system, the ethoxy group of KH-550 is hydrolyzed to generate silanol groups, which then undergo a condensation reaction with the silanol groups on the surface of nano-SiO2, introducing active groups onto the surface of nano-SiO2 and preparing an aminated functionalized nano-SiO2 dispersion.

[0028] The functionalized nano-SiO2 (S3, covalently grafted with nano-SiO2) achieves chemical bonding with the surface of activated coal gangue through KH-550 molecular bridges, with the amino groups at the ends of KH-550 exposed. This step upgrades the traditional physical doping of nano-SiO2 to chemical bonding and anchoring, solving the problems of easy agglomeration and desorption of nanoparticles from the aggregate surface in direct mixing methods.

[0029] S4 (In-situ Deposition of Nano-CaCO3) involves immersing coal gangue grafted with nano-SiO2 into a Ca(OH)2 solution. Utilizing the negatively charged surface of the SiO2 layer under alkaline conditions, Ca is electrostatically enriched. 2+ Then CO2 is introduced to make Ca2+ In situ, the SiO2 layer is transformed into nano-CaCO3 on its surface. The surface of the nano-SiO2 layer provides a large number of low-energy nucleation sites, which promotes the preferential heterogeneous nucleation of CaCO3 on the SiO2 layer surface, inhibiting the formation of a large number of homogeneous grains in the liquid phase, and forming a dual nanogradient structure of aggregate—covalent bond—nano-SiO2 inner layer—in situ deposited nano-CaCO3 outer shell. This structure realizes the stepwise functionalization of the aggregate surface: the inner SiO2 layer plays a role in pozzolanic activity and provides nucleation sites, while the outer CaCO3 layer plays a role in early nucleation induction and micro-aggregate filling. The two work together to strengthen the transition zone of the aggregate-mortar interface.

[0030] S5 (pre-mixed aggregate) involves pre-mixing dual nano-gradient modified coal gangue with an alkali activator (NaOH + water glass) for 1-2 hours, allowing the alkali activator to fully penetrate the surface of the coal gangue and activate its potential pozzolanic activity; at the same time, it avoids the conflict of setting time caused by premature cement hydration, and provides an aggregate skeleton with fully activated activity for subsequent secondary mixing.

[0031] S6 (Forced Mixing) involves forcibly mixing the pre-cured material with silicate cement, phosphogypsum, water, polycarboxylate superplasticizer, and ethylene-vinyl acetate (EVA) copolymer latex powder. The components create multiple synergistic effects: phosphogypsum dissolves SO4. 2- Together with the alkali activator, it forms an alkali-sulfate composite activation system, promoting cement hydration and ettringite formation. This, combined with the nucleation effect of the nano-SiO2 layer, creates a synergistic effect of sulfate activation and nano-heterogeneous nucleation. EVA latex powder forms a polymer film upon contact with water. The amino groups on its molecular chains form dense hydrogen bonds with the amino groups exposed on the surface of the nano-SiO2 layer in step S3, achieving a tight bond between the flexible polymer film and the rigid inorganic nano-gradient interface, constructing a rigid nano-reinforcement layer-flexible polymer network composite interface. The SO4 released by phosphogypsum... 2- With Ca in the system 2+ It participates in the hydration reaction and, together with cement hydration products, nano-CaCO3 shell and alkali-activated components, constructs an alkali-sulfur-nano-calcium multi-element synergistic hydration system.

[0032] It is important to emphasize that the grafted amino (-NH2) nano-SiO2 surface layer plays a role in inducing nucleation in stage S4, anchoring nano-CaCO3 in situ to the SiO2 layer surface. In stage S6, the CaCO3 shell plays a triple role of guiding, anchoring, and strengthening. Its nanopores guide EVA chains to penetrate and reach the amino group to form hydrogen bonds, while its rigid grains are embedded in the polymer film to provide mechanical interlocking and stress buffering. Ultimately, the amino group, nano-CaCO3, and EVA form a tightly integrated whole. The inner SiO2 layer provides pozzolanic activity and rigid support, the outer CaCO3 layer provides early nucleation effect and forms mechanical interlocking with the polymer, and the EVA polymer film achieves flexible buffering through hydrogen bond crosslinking. The three work synergistically to achieve a simultaneous improvement in crack resistance and strength.

[0033] S7 (forming and curing) uses vibration compaction to achieve a compaction degree of ≥98% in the mixture, forming a dense skeleton structure; the moist curing stage continuously promotes cement hydration and alkali-activated reaction, while the hydrogen bond network between the EVA polymer film and the inorganic interface is continuously stabilized, enabling the dual nano-gradient inorganic interface, polymer toughening network and cementitious matrix to develop synergistically, ultimately forming a high-strength, high-crack-resistant and high-water-stability road base material.

[0034] In some embodiments, by weight, the coal gangue-based solid waste road base mixture contains 65-80 parts of coal gangue aggregate, 8-12 parts of silicate cement, 3-6 parts of phosphogypsum, 0.9-1.8 parts of alkali activator, 0.5-1.0 parts of polycarboxylate superplasticizer, and 0.15-0.45 parts of ethylene-vinyl acetate copolymer latex powder.

[0035] Coal gangue aggregate (65-80 parts) forms the main skeleton, ensuring a solid waste disposal rate of ≥70% while providing ample space for the cementitious materials to form a dense skeleton structure; silicate cement (8-12 parts) serves as the main cementitious component, and with the synergistic effect of alkali activation and sulfate, strength development can be guaranteed with a relatively low dosage, aligning with low-carbon goals; phosphogypsum (3-6 parts) is dissolved. The alkali-sulfate composite activation system is formed with the alkali activator to promote the formation of ettringite and synergize with the nucleation sites of nano-SiO2, thus refining the crystal size of ettringite. 0.9 to 1.8 parts of the alkali activator activate the potential pozzolanic activity of coal gangue and, together with cement and phosphogypsum, construct a multi-component synergistic hydration system. 0.15 to 0.45 parts of EVA latex powder, after forming a film upon contact with water, form dense hydrogen bonds with the amino groups on the surface of grafted nano-SiO2, constructing a composite interface between a flexible polymer network and a rigid nano-reinforcing layer. 0.5 to 1.0 parts of polycarboxylate superplasticizer optimize workability, reduce mixing water consumption, and improve density.

[0036] In some embodiments, the concentration of the NaOH solution is 10–20 wt%; The activation pretreatment is performed at a temperature of 60–80°C for 2–4 hours.

[0037] With a NaOH concentration of 10–20 wt%, a temperature of 60–80 °C, and a time of 2–4 h, the alkaline solution gently etches the surface of coal gangue, dissolving the amorphous silica-alumina components on the surface, fully exposing and generating sufficient silanol and aluminol active sites, providing ample chemical reaction sites for subsequent covalent grafting.

[0038] In some embodiments, the mass of the nano-SiO2 is 0.4% to 0.9% of the mass of the coal gangue aggregate; The mass of the silane coupling agent KH-550 is 5% to 10% of the mass of the nano-SiO2.

[0039] Nano-SiO2 accounts for 0.4% to 0.9% of the mass of coal gangue aggregate. With a small amount, a complete covalent grafted coating layer can be formed on the surface of the aggregate, giving full play to the activity and nucleation site function of pozzolanic ash, demonstrating the high efficiency of chemical grafting compared with physical doping; KH-550 accounts for 5% to 10% of the mass of nano-SiO2, ensuring that the surface of nano-SiO2 is fully functionalized and introducing sufficient amino active groups.

[0040] In some embodiments, the temperature of the stirring reaction is 80–100°C, and the time is 1–2 hours.

[0041] The stirring reaction is carried out at a temperature of 80-100℃ for 1-2 hours. Under these conditions, the dehydration condensation reaction of the silanol groups at both ends of KH-550 with the hydroxyl groups on the surface of coal gangue and the hydroxyl groups on the surface of nano-SiO2 is fully carried out, forming stable Si-O-Si covalent bonds, ensuring that nano-SiO2 is firmly anchored to the surface of the aggregate through molecular bridges.

[0042] In some embodiments, the concentration of the Ca(OH)2 solution is 0.02–0.05 mol / L, and the soaking time is 10–30 min.

[0043] In some embodiments, the purity of the CO2 gas is ≥99%, the flow rate is 0.5–2.0 L / min, the introduction time is 10–40 min, the reaction temperature is 25–60 °C, and the reaction endpoint is when the pH of the system drops to 10.0–10.5.

[0044] The Ca(OH)₂ solution concentration is 0.02–0.05 mol / L, and the soaking time is 10–30 min. Under these conditions, Ca… 2+ Electrostatic enrichment on the SiO2 layer surface reaches saturation, providing a sufficient and uniform calcium source for subsequent carbonization reactions; CO2 purity ≥99%, flow rate 0.5–2.0 L / min, introduction time 10–40 min, temperature 25–60 °C, these mild carbonization conditions allow Ca to... 2+ The SiO2 layer slowly transforms into nano-CaCO3 on its surface, ensuring small and uniform grain size and preferential heterogeneous nucleation. The pH drops to 10.0-10.5 as the reaction endpoint, effectively avoiding excessive carbonization that would cause CaCO3 to transform into soluble Ca(HCO3)2.

[0045] In some embodiments, the alkaline activator is a composite activator of NaOH and water glass, wherein the mass ratio of NaOH to water glass is 1:(1-3), and the modulus of water glass is 1.0-1.5.

[0046] The mass ratio of NaOH to water glass is 1:1 to 3, and the modulus of water glass is 1.0 to 1.5. This ratio provides a suitable alkaline environment and soluble silicates, which can effectively activate the activity of coal gangue and react with the SO4 dissolved from phosphogypsum. 2- A synergistic activating effect between alkali and sulfate is formed, promoting the formation of hydration products.

[0047] In some embodiments, the particle size range of the coal gangue aggregate is 0.075 to 31.5 mm, and a four-stage gradation is adopted. By mass fraction, 31.5 to 19 mm accounts for 25% to 35%, 19 to 9.5 mm accounts for 35% to 45%, 9.5 to 4.75 mm accounts for 10% to 15%, and less than 4.75 mm accounts for 10% to 15%.

[0048] In the four-stage gradation, 25%–35% of the coarse aggregate (31.5–19 mm) forms the main skeleton, 35%–45% of the 19–9.5 mm aggregate fills the gaps in the coarse skeleton, 10%–15% of the 9.5–4.75 mm aggregate further densifies the skeleton, and 10%–15% of the aggregate (below 4.75 mm) fills the fine pores. This process achieves a gradual filling from coarse to fine, forming a dense skeleton structure and ensuring that the porosity is minimized after compaction.

[0049] Based on a general inventive concept, this application provides a coal gangue-based solid waste road base course mixture prepared by any of the methods described above, wherein the 7-day unconfined compressive strength of the coal gangue-based solid waste road base course mixture is 4.5–6.5 MPa, and the 28-day unconfined compressive strength is 6.0–8.5 MPa.

[0050] The 7-day unconfined compressive strength of the coal gangue-based solid waste pavement base course mixture in this application reaches 4.5–6.5 MPa, and the 28-day unconfined compressive strength reaches 6.0–8.5 MPa. This strength level is achieved due to the combined effect of multiple synergistic enhancement mechanisms.

[0051] (1) Interface enhancement effect of dual nanogradient modification After nano-SiO2 is chemically grafted onto the surface of coal gangue aggregate via KH-550 molecular bridges using Si-O-Si covalent bonds, it plays the following roles: Nano-SiO2 induces the formation of cement hydration products, accelerating the hydration process and promoting CSH gel growth; Nano-SiO2 exhibits pozzolanic activity, reacting with calcium hydroxide produced during cement hydration to generate secondary hydration products, reducing the orientation of calcium hydroxide crystals at the aggregate-cement stone interface; The micro-aggregate filling effect of nano-SiO2 effectively fills the nanoscale pores in the interfacial transition zone. These three effects collectively strengthen the interfacial transition zone between the aggregate and cementitious materials, causing the hydration products to be tightly arranged in the interfacial region, forming a dense network microstructure and reducing porosity.

[0052] The nano-CaCO3 shell deposited in situ on the surface of the nano-SiO2 layer exerts an early strengthening effect through the nucleation effect. Nano-CaCO3 accelerates the cement hydration induction period, shifting the second peak of the exothermic hydration process earlier. The nucleation effect of nano-CaCO3 preferentially adsorbs calcium and hydroxide ions in the slurry onto its surface, leading to the initial nucleation of calcium hydroxide crystals with reduced orientation, thus promoting the hydration and growth of tricalcium silicate in the interfacial transition zone. Furthermore, the micro-aggregate filling effect of nano-CaCO3 further reduces porosity in the interfacial region. The inner SiO2 layer continues to exert pozzolanic activity in the middle and later stages of hydration, while the outer CaCO3 layer exerts a nucleation effect in the early stages of hydration. These two layers complement each other over time, achieving strength development throughout the entire lifespan from early to middle and late stages.

[0053] (2) The full activation of coal gangue activity by the alkali-sulfate composite activation system Alkali activators and phosphogypsum together constitute an alkali-sulfate composite activation system. Under the action of the alkali activator, the aluminosilicate structure in coal gangue is destroyed, and it synergistically generates sodium aluminosilicate hydrate (NASH), calcium aluminosilicate hydrate (CASH), and calcium silicate hydrate (CSH) gels with calcium ions produced during cement hydration. These gels intertwine to form a dense microstructure. Sulfate ions dissolved from phosphogypsum react with tricalcium aluminate in cement to form ettringite. Under the action of nucleation sites provided by the surface of the nano-SiO2 layer, the nucleation and growth of ettringite crystals are regulated, resulting in finer grain size and more uniform distribution. The CSH gel, CASH gel, NASH gel, and ettringite crystals are tightly intertwined at the microscale, reducing the total porosity in the cement paste. The hydration products of the high-dosage phosphogypsum system are also mainly CSH gel and ettringite. The alkali activator not only activates the cement but also further generates CSH gel and calcium aluminosilicate hydrate gel with calcium ions in phosphogypsum through a pozzolanic reaction.

[0054] (3) Interfacial toughening and synergistic reinforcement of polymer films When ethylene-vinyl acetate copolymer latex powder reacts with water to form a polymer film, its molecular chains form dense hydrogen bonds with the exposed amino groups on the grafted nano-SiO2 surface, achieving a tight bond between the flexible polymer film and the rigid inorganic nanogradient interface. This composite interface allows the polymer film to provide both flexibility and cushioning while simultaneously forming an effective force transmission channel with the inorganic reinforcing layer through a hydrogen bond network. The flexible nature of the polymer film buffers the reciprocating stress of coal gangue aggregate during water absorption and drying, while the hydrogen bonds prevent interfacial debonding between the flexible and rigid layers. Together, these properties provide the material with sufficient rigid support and a certain degree of deformation tolerance under load.

[0055] (4) Synergistic superposition of multi-component hydration products The hydration of silicate cement provides CSH gel and calcium hydroxide. Nano-SiO2 consumes calcium hydroxide to generate additional CSH gel. Alkali activators stimulate the formation of NASH and CASH gels from coal gangue. Phosphogypsum provides sulfate ions to promote ettringite formation. Nano-CaCO3 provides nucleation sites to accelerate the hydration process. The hydration products of each component do not exist independently, but rather interpenetrate and grow synergistically at the microscale. CSH gel, CASH gel, NASH gel, and ettringite crystals together form a dense cementitious network. This synergistic effect of the multi-component hydration products results in significantly superior 7-day and 28-day strengths compared to a single cement-based cementitious system.

[0056] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards. If there is no corresponding industry standard, then common international standards, conventional conditions, or conditions recommended by the manufacturer are followed.

[0057] Example 1: In this example, the components of the coal gangue-based solid waste roadbed mixture are prepared according to the following mass proportions: 72 parts coal gangue aggregate; 10 parts P·O 42.5 grade ordinary Portland cement; 4.5 parts phosphogypsum; 1.2 parts alkali activator (0.4 parts NaOH, 0.8 parts water glass, water glass modulus 1.2); 0.8 parts polycarboxylate superplasticizer; 0.3 parts ethylene-vinyl acetate copolymer latex powder; water adjusted to a moisture content of 12%.

[0058] Among them, the coal gangue aggregate adopts a four-stage gradation, which is calculated by mass fraction as follows: 30% of the particle size is 31.5-19mm, 40% is 19-9.5mm, 13% is 9.5-4.75mm, and 17% is below 4.75mm.

[0059] Phosphogypsum is an industrial by-product, dried at 105℃ and ground to a specific surface area ≥350m². 2 / kg, P2O5 content ≤1.0%.

[0060] Based on the above-mentioned components of the coal gangue-based solid waste roadbed mixture, this embodiment also provides a preparation method, including the following steps: S1. The coal gangue aggregate is soaked in a 15wt% NaOH solution and treated at 70℃ for 3 hours to allow the alkaline solution to gently etch the surface of the coal gangue. After activation, the aggregate is repeatedly washed with deionized water until the pH is 7-8, and then dried at 90℃ until the moisture content is <1% to obtain activated coal gangue.

[0061] S2. Add nano-SiO2 (0.64% of the coal gangue aggregate mass, particle size 10-50nm, specific surface area ≥150m² / g, purity ≥99.5%) to a mixed solvent of ethanol and water in a volume ratio of 1:1, add silane coupling agent KH-550 (8% of the nano-SiO2 mass), and ultrasonically disperse for 30min to obtain functionalized nano-SiO2 dispersion.

[0062] S3. The activated coal gangue was mixed with the functionalized nano-SiO2 dispersion and stirred at 90°C for 1.5 h. After the reaction was completed, the ungrafted nano-SiO2 was removed by washing with water and then dried to obtain nano-SiO2-grafted coal gangue.

[0063] S4. Immerse the nano-SiO2-grafted coal gangue in a 0.035 mol / L Ca(OH)2 solution for 20 minutes, allowing the Ca... 2+ The carbonization reaction was carried out at 40°C for 25 minutes, with CO2 gas of ≥99% purity introduced into the system at a flow rate of 1.2 L / min until the pH of the system dropped to 10.3. After the reaction was completed, the mixture was washed with deionized water and dried to obtain the dual nanogradient modified coal gangue.

[0064] S5. Mix the dual nanogradient modified coal gangue with an alkali activator and 65% of the total water volume of water, and let it stand for 1.5 hours to obtain a pre-cured mixture.

[0065] S6. Add the pre-cured mixture, silicate cement, phosphogypsum, excess water, polycarboxylate superplasticizer, and EVA latex powder to the mixer and force mix for 150 seconds. The total time from adding water and mixing to the completion of compaction should be controlled within 2 hours.

[0066] S7. Compact the well-mixed material using a high-frequency vibratory roller with a vibration frequency of 50Hz, an amplitude of 0.6mm, and a compaction degree of ≥98%. After molding, cover with a moisturizing and curing film and water for 7 days.

[0067] Example 2: This example provides a coal gangue-based solid waste road base mixture and its preparation method. The components are prepared in the following proportions by weight: 65 parts coal gangue aggregate, 12 parts P·O 42.5 grade ordinary Portland cement, 6 parts phosphogypsum, 1.8 parts alkali activator (0.6 parts NaOH, 1.2 parts water glass, water glass modulus 1.2), 1.0 part polycarboxylate superplasticizer, 0.45 parts ethylene-vinyl acetate copolymer latex powder, and water adjusted to a moisture content of 11%.

[0068] The coal gangue aggregate adopts a four-stage gradation, which is calculated by mass fraction as follows: 25% of the particles are 31.5-19mm, 45% are 19-9.5mm, 15% are 9.5-4.75mm, and 15% are below 4.75mm.

[0069] Based on the above-mentioned components of the coal gangue-based solid waste road base mixture, this embodiment also provides a preparation method, including the following steps: S1. The coal gangue aggregate is soaked in a 10wt% NaOH solution and treated at 80℃ for 4 hours to allow the alkaline solution to gently etch the surface of the coal gangue. After activation, the aggregate is repeatedly washed with deionized water until the pH reaches 7-8, and then dried at 90℃ until the moisture content is <1% to obtain activated coal gangue.

[0070] S2. Add nano-SiO2 (0.9% of the mass of coal gangue aggregate) to a mixed solvent of ethanol and water in a volume ratio of 1:1, add silane coupling agent KH-550 (10% of the mass of nano-SiO2), and ultrasonically disperse for 30 min to obtain functionalized nano-SiO2 dispersion.

[0071] S3. The activated coal gangue was mixed with the functionalized nano-SiO2 dispersion and stirred at 80°C for 2 hours. After the reaction was completed, the ungrafted nano-SiO2 was removed by washing with water and then dried to obtain nano-SiO2-grafted coal gangue.

[0072] S4. Immerse the nano-SiO2-grafted coal gangue in a 0.02 mol / L Ca(OH)2 solution for 30 minutes, so that the Ca... 2+ The carbonization reaction was carried out at 25°C for 40 minutes after CO2 gas with a purity of ≥99% was introduced into the system at a flow rate of 2.0 L / min until the pH of the system dropped to 10.0. After the reaction was completed, the mixture was washed with deionized water and dried to obtain the dual nanogradient modified coal gangue.

[0073] S5. Mix the dual nanogradient modified coal gangue with an alkali activator and 60% of the total water volume, and let it stand for 1 hour to obtain a pre-fermented mixture.

[0074] S6. Add the pre-cured mixture, silicate cement, phosphogypsum, excess water, polycarboxylate superplasticizer, and EVA latex powder to the mixer and force mix for 120 seconds. The total time from adding water and mixing to the completion of compaction should be controlled within 2 hours.

[0075] S7. Compact the well-mixed material using a high-frequency vibratory roller with a vibration frequency of 40Hz, an amplitude of 0.8mm, and a compaction degree of ≥98%. After molding, cover with a moisturizing and curing film and spray water for 7 days.

[0076] Example 3: This example provides a coal gangue-based solid waste road base mixture and its preparation method. The components are prepared in the following proportions by weight: 80 parts coal gangue aggregate, 8 parts P·O 42.5 grade ordinary Portland cement, 3 parts phosphogypsum, 0.9 parts alkali activator (0.3 parts NaOH, 0.6 parts water glass, water glass modulus 1.2), 0.5 parts polycarboxylate superplasticizer, 0.15 parts ethylene-vinyl acetate copolymer latex powder, and water adjusted to a moisture content of 13%.

[0077] Among them, the coal gangue aggregate adopts a four-stage gradation, which is calculated by mass fraction as follows: 35% of the particles are 31.5-19mm, 35% are 19-9.5mm, 10% are 9.5-4.75mm, and 20% are below 4.75mm.

[0078] Based on the above-mentioned components of the coal gangue-based solid waste road base mixture, this embodiment also provides a preparation method, including the following steps: S1. The coal gangue aggregate is soaked in a 20wt% NaOH solution and treated at 60℃ for 2 hours to allow the alkaline solution to gently etch the surface of the coal gangue. After activation, the aggregate is repeatedly washed with deionized water until the pH reaches 7-8, and then dried at 90℃ until the moisture content is <1% to obtain activated coal gangue.

[0079] S2. Add nano-SiO2 (0.4% of the mass of coal gangue aggregate) to a mixed solvent of ethanol and water in a volume ratio of 1:1, add silane coupling agent KH-550 (5% of the mass of nano-SiO2), and ultrasonically disperse for 30 min to obtain functionalized nano-SiO2 dispersion.

[0080] S3. The activated coal gangue was mixed with the functionalized nano-SiO2 dispersion and stirred at 100°C for 1 hour. After the reaction was completed, the ungrafted nano-SiO2 was removed by washing with water and then dried to obtain nano-SiO2-grafted coal gangue.

[0081] S4. Immerse the nano-SiO2-grafted coal gangue in a 0.05 mol / L Ca(OH)2 solution for 10 minutes, so that the Ca... 2+ The carbonization reaction was carried out at 60°C for 10 minutes, with CO2 gas of ≥99% purity introduced into the system at a flow rate of 0.5 L / min until the pH of the system dropped to 10.5. After the reaction was completed, the mixture was washed with deionized water and dried to obtain double nanogradient modified coal gangue.

[0082] S5. Mix the dual nanogradient modified coal gangue with an alkali activator and 70% of the total water volume, and let it stand for 2 hours to obtain a pre-fermented mixture.

[0083] S6. Add the pre-cured mixture, silicate cement, phosphogypsum, excess water, polycarboxylate superplasticizer, and EVA latex powder to the mixer and force mix for 180 seconds. The total time from adding water and mixing to the completion of compaction should be controlled within 2 hours.

[0084] S7. Compact the well-mixed material using a high-frequency vibratory roller with a vibration frequency of 60Hz, an amplitude of 0.4mm, and a compaction degree of ≥98%. After molding, cover with a moisturizing and curing film and spray water for 7 days.

[0085] Comparative Example 1 This comparative example is modified from the one disclosed in Example 1 as follows: The covalent grafting and in-situ deposition process of nano-SiO2 in steps S3 and S4 was cancelled. Instead, an equal amount of nano-SiO2 (0.64% of the coal gangue aggregate mass) and an equal amount of nano-CaCO3 (0.96% of the coal gangue aggregate mass) were directly added in powder form in the forced mixing stage of S6 along with other dry materials. The remaining components, dosages, and preparation steps were kept the same as in Example 1.

[0086] Comparative Example 2 This comparative example is modified from the one disclosed in Example 1 as follows: The in-situ deposition process of nano-CaCO3 in step S4 is cancelled. That is, after completing steps S1 to S3 to obtain nano-SiO2 grafted coal gangue, the process directly enters the pre-curing step S5 without soaking in Ca(OH)2 solution and CO2 carbonization reaction. The remaining components, dosages, and preparation steps are consistent with those in Example 1.

[0087] Comparative Example 3 This comparative example is modified from the one disclosed in Example 1 as follows: The nano-SiO2 covalent grafting process in step S3 is omitted. That is, after the coal gangue aggregate is activated by alkali in step S1, the nano-SiO2 grafting reaction is not carried out. Instead, it directly enters step S4 for in-situ deposition of nano-CaCO3 (the activated coal gangue is directly immersed in Ca(OH)2 solution and then carbonized by passing CO2 through it). The remaining components, dosages, and preparation steps are consistent with those in Example 1.

[0088] Comparative Example 4 This comparative example is modified from the one disclosed in Example 1 as follows: The ethylene-vinyl acetate copolymer latex powder component in step S6 was removed, while the remaining components, dosages, and preparation steps remained the same as in Example 1.

[0089] Comparative Example 5 This comparative example is modified from the one disclosed in Example 1 as follows: The alkali activator component in step S5 is removed. In step S5, the dual nanogradient modified coal gangue is directly mixed with water equal to 65% of the total water volume and left to stand for 1.5 hours. The remaining components, dosages, and preparation steps are consistent with those in Example 1.

[0090] The performance of coal gangue-based solid waste pavement base course mixtures obtained in Examples 1-3 and Comparative Examples 1-5 was determined in accordance with the "Test Procedure for Inorganic Binder Stabilized Materials in Highway Engineering" (JTG E51-2009). The results are shown in Table 1.

[0091] Table 1. Performance of coal gangue-based solid waste pavement base course mixtures in Examples 1-3 and Comparative Examples 1-5

[0092] As shown in Table 1, the 7-day unconfined compressive strength of Examples 1-3 is 4.8-5.7 MPa, the 28-day unconfined compressive strength is 6.3-7.8 MPa, the strength loss rate after 5 freeze-thaw cycles is 13.1%-18.2%, and the drying shrinkage coefficient is 1.65-2.19×10⁻⁶. -4 .

[0093] Comparative Example 1, where nanomaterials were replaced with powder directly incorporated, resulted in nanoparticles failing to form strong chemical bonds and gradient interfaces on the aggregate surface, leading to the lowest strength and a significantly increased freeze-thaw loss rate. Its shrinkage coefficient was only slightly lower than Comparative Example 5, which lacked the alkali activator. Comparative Example 2, lacking a nano-CaCO3 shell, exhibited higher interfacial porosity and a missing early nucleation effect, resulting in a significant decrease in all properties compared to Example 1. Comparative Example 3, lacking a nano-SiO2 inner layer, lacked the pozzolanic activity and rigid support in the interfacial transition zone, resulting in lower strength and durability than Comparative Example 2. This indicates that the SiO2 inner layer contributes more to interfacial reinforcement than the CaCO3 shell. Comparative Example 4, lacking the flexible buffering and hydrogen-bonded crosslinking toughening effect of the EVA polymer film, significantly weakened its shrinkage suppression effect, achieving a shrinkage coefficient of 2.86 × 10⁻⁶. -4 However, the remaining properties are still better than those of Comparative Examples 1-3, indicating that EVA mainly contributes to crack resistance and has a small contribution to mechanical strength; after removing the alkali activator, the activity of coal gangue in Comparative Example 5 was not activated, the cementitious products were insufficient, and all properties were the worst.

[0094] Figure 2 Infrared spectra of raw coal gangue, nano-SiO2 grafted coal gangue, and dual nanogradient modified coal gangue provided in Example 1 of this application.

[0095] Depend on Figure 2 It can be seen that the original coal gangue was at approximately 3400 cm. -1 An absorption peak at approximately 1100 cm⁻¹ appears, attributed to the OH stretching vibration in aluminosilicate minerals. -1A strong absorption peak for the Si-O-Si asymmetric stretching vibration appears at approximately 800 cm⁻¹. -1 and 470 cm -1 The presence of Si-O bending vibration peaks indicates that the original coal gangue surface is dominated by a silicon-oxygen framework.

[0096] Compared to raw coal gangue, after grafting with S3 nano-SiO2, approximately 3400 cm³ -1 The significantly enhanced intensity and broadened peak shape of the OH peak at approximately 2920 cm⁻¹ are attributed to the superposition of silanol groups exposed by alkali activation and hydroxyl groups remaining from the grafting reaction; -1 and 2850cm -1 The newly appearing stretching vibration absorption peak of the methylene group (-CH2-) appears at approximately 1560 cm⁻¹. -1 The newly observed weak absorption peak of NH bending vibration confirms that the propyl segment and terminal amino group of the silane coupling agent KH-550 were successfully introduced into the aggregate surface; simultaneously, at approximately 1100 cm⁻¹ -1 The Si-O-Si peaks were significantly broadened and enhanced, reflecting that nano-SiO2 was firmly grafted onto the surface of coal gangue through Si-O-Si covalent bonds.

[0097] Compared to the grafted state, after in-situ deposition of S4 nanometer CaCO3, the thickness was approximately 2920 cm². -1 2850 cm -1 and 1560 cm -1 The retention of the peak position indicates that the nano-SiO2 grafted layer structure remains stable during carbonization; at approximately 1420 cm⁻¹ -1 A strong and broad absorption peak appears at approximately 875 cm⁻¹, which is attributed to the CO asymmetric stretching vibration of calcite-type CaCO₃; -1 and 712 cm -1 The newly appearing absorption peaks are attributed to out-of-plane and in-plane bending vibrations of CO, respectively, confirming the successful in-situ deposition of nano-CaCO3 on the surface of nano-SiO2 layer.

[0098] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the referred range.

[0099] Furthermore, in the description of this application, the terms "comprising," "including," etc., mean "including but not limited to." In this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations.

[0100] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a coal gangue-based solid waste roadbed mixture, characterized in that, The method includes the following steps: S1. The coal gangue aggregate is soaked in NaOH solution for activation pretreatment to obtain activated coal gangue; S2. Add nano-SiO2 and silane coupling agent KH-550 to an ethanol-water mixed solvent to obtain a functionalized nano-SiO2 dispersion. S3. The activated coal gangue and the functionalized nano-SiO2 dispersion are stirred and reacted to obtain nano-SiO2 grafted coal gangue. S4. The nano-SiO2-grafted coal gangue is immersed in Ca(OH)2 solution, and then CO2 gas is introduced into the system to carry out carbonization reaction to obtain dual nanogradient modified coal gangue. S5. The dual nanogradient modified coal gangue is mixed with alkali activator and water and then subjected to static curing treatment to obtain pre-cured mixture. S6. The pre-cured mixture is subjected to forced mixing with silicate cement, phosphogypsum, water, polycarboxylate superplasticizer, and ethylene-vinyl acetate copolymer latex powder to obtain a mixture. S7. The mixture is subjected to vibration compaction and curing treatment to obtain coal gangue-based solid waste road base mixture.

2. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, By weight, the coal gangue-based solid waste road base mixture contains 65-80 parts coal gangue aggregate, 8-12 parts silicate cement, 3-6 parts phosphogypsum, 0.9-1.8 parts alkali activator, 0.5-1.0 parts polycarboxylate superplasticizer, and 0.15-0.45 parts ethylene-vinyl acetate copolymer latex powder.

3. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The concentration of the NaOH solution is 10–20 wt%. The activation pretreatment is performed at a temperature of 60–80°C for 2–4 hours.

4. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The mass of the nano-SiO2 is 0.4% to 0.9% of the mass of the coal gangue aggregate; The mass of the silane coupling agent KH-550 is 5% to 10% of the mass of the nano-SiO2.

5. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The stirring reaction is carried out at a temperature of 80–100°C for 1–2 hours.

6. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The concentration of the Ca(OH)2 solution is 0.02–0.05 mol / L, and the soaking time is 10–30 min.

7. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The CO2 gas has a purity of ≥99%, a flow rate of 0.5–2.0 L / min, an introduction time of 10–40 min, a reaction temperature of 25–60 °C, and the reaction endpoint is when the pH of the system drops to 10.0–10.

5.

8. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The alkaline activator is a composite activator of NaOH and water glass, with a mass ratio of NaOH to water glass of 1:(1-3) and a water glass modulus of 1.0-1.

5.

9. The method for preparing the coal gangue-based solid waste roadbed mixture according to claim 1, characterized in that, The coal gangue aggregate has a particle size range of 0.075–31.5 mm and adopts a four-stage gradation. By mass fraction, 31.5–19 mm accounts for 25%–35%, 19–9.5 mm accounts for 35%–45%, 9.5–4.75 mm accounts for 10%–15%, and less than 4.75 mm accounts for 10%–15%.

10. A coal gangue-based solid waste roadbed mixture prepared by the method according to any one of claims 1 to 9, characterized in that, The 7-day unconfined compressive strength of the coal gangue-based solid waste road base mixture is 4.5–6.5 MPa, and the 28-day unconfined compressive strength is 6.0–8.5 MPa.